Asked by chandant | 18th Apr, 2010, 03:34: PM

Expert Answer:

Dear Student,

The solution to your problem is as follows -

Let A and B be two non-empty (or non-null) matrices.

By the hypothesis of the question, AB=0

Now, Assume that A is non-singular.

=> A-1 exists.

Therefore, multiply both sides of equation by A-1

=> A-1AB=0

=> B=0

But this is a contradiction to the fact that B is non-empty matrix. Hence A can't be non-singular matrix.


Similarly, assume B to be non singular.

=> B-1 exists.

Multiply both sides by B-1,

=> ABB-1=0

=> A=0

Again, this is contradiction to the fact that A is non-empty. Therefore, B can't be non-singular.


Regards Topperlearning.

Answered by  | 22nd Apr, 2010, 11:00: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.